1994
DOI: 10.1002/bip.360340215
|View full text |Cite
|
Sign up to set email alerts
|

Rheological properties and conformational states of β‐conglycinin gels at acidic pH

Abstract: SYNOPSISThe heat-induced gelation of P-conglycinin was investigated by dynamic viscoelastic measurements as a function of pH. At pH values below 5.5-6.0, the storage modulus G' rapidly increased with decreasing pH. The conformational states of both sols and gels of @-conglycinin were investigated by Fourier transform ir (FTIR) and by differential scanning calorimetry (DSC). The degree of protonation of the carboxyl groups of P-conglycinin, when examined by FTIR indicated that, as would be expected, the degree … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 29 publications
4
23
0
Order By: Relevance
“…The pH-dependent trends in HCTs in these emulsion results are consistent with those found by Hermansson (1977), Hermansson (1978), Iwabuchi, Watanabe, and Yamauchi (1991), Mohamed and Xu (2003) and Ryan et al (2008), where intact soy protein dispersions were found to be more heat stable at alkaline than at acidic pH. Nagano, Mori, and Nishinari (1994) also reported that lowering the pH caused the denaturation temperature of SPI, glycinin and b-conglycinin to shift to lower values which may, in part, also explain the results obtained. From Fig.…”
Section: Heat Coagulation Time (Hct) Of Model Emulsionssupporting
confidence: 92%
See 2 more Smart Citations
“…The pH-dependent trends in HCTs in these emulsion results are consistent with those found by Hermansson (1977), Hermansson (1978), Iwabuchi, Watanabe, and Yamauchi (1991), Mohamed and Xu (2003) and Ryan et al (2008), where intact soy protein dispersions were found to be more heat stable at alkaline than at acidic pH. Nagano, Mori, and Nishinari (1994) also reported that lowering the pH caused the denaturation temperature of SPI, glycinin and b-conglycinin to shift to lower values which may, in part, also explain the results obtained. From Fig.…”
Section: Heat Coagulation Time (Hct) Of Model Emulsionssupporting
confidence: 92%
“…For example, the heat-induced aggregation behavior (40-100°C) of soy b-conglycinin in the presence of 2.5% (w/v) NaCl has been attributed to a reduction in the net surface charge density of the denatured protein promoting hydrophobic aggregation (Nagano et al, 1994). Furthermore, the observed decrease in HCT of milk protein on supplementation with Ca 2+ was attributed to the shielding of negative charges inducing a reduction in electrostatic repulsion between protein molecules leading to their subsequent aggregation (McCrae & Muir, 1995).…”
Section: Effect Of Addition Of Calcium Salts On Hctmentioning
confidence: 99%
See 1 more Smart Citation
“…Their functional properties are used mainly to form three-dimensional networks such as hydrogels. A range of methods for gelling soy protein have been developed, from thermal gelation (Hermansson, 1985;Nagano, Akasaka, & Nishinari, 1994;Nagano, Hirotsuka, Mori, Kohyama, & Nishinari, 1992;Nagano, Mori, & Nishinari, 1994;Renkema, 2004;Renkema, Gruppen, & van Vliet, 2002;Renkema, Knabben, & van Vliet, 2001;Renkema, Lakemond, de Jongh, Gruppen, & van Vliet, 2000;Renkema & van Vliet, 2004;van Vliet, Martin, & Bos, 2002) to cold-set hydrogel formation (Maltais, Remondetto, Gonzalez, & Subirade, 2005;Maltais, Remondetto, & Subirade, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Both FTIR and DSC have been used to study the structure and conformation of buckwheat globulin (Choi & Ma, 2005), soybean glycinin and b-conglycinin (Nagano, Akasaka, & Nishinari, 1995;Nagano, Mori, & Nishinari, 1994;Petruccelli & Añón, 1996), b-lactoglobulin (Boye, Ma, & Ismail, 1998;Boye, Ma, & Ismail, 2004), oat globulin (Harwalkar & Ma, 1987;Ma, Rout, & Mock, 2001) and bovine serum albumin (Boye, Alli, & Ismail, 1996).…”
Section: Introductionmentioning
confidence: 99%